Inseparable : a never-before-published novel - Beauvoir, Simone de, 1908-1986 (Ecco, an imprint of HarperCollinsPublishers, 2021)
"Deemed too intimate to publish during Simone de Beauvoir's life, Inseparable offers fresh insight into the groundbreaking feminist's own coming-of-age; her transformative, tragic friendship with her childhood friend Zaza Lacoin; and how her youthful relationships shaped her philosophy. Sandra Smith's vibrant translation of the novel will be long cherished by de Beauvoir devotees and first-time readers alike"--